2017
DOI: 10.1097/bcr.0000000000000610
|View full text |Cite
|
Sign up to set email alerts
|

Resting β-Adrenergic Blockade Does Not Alter Exercise Thermoregulation in Children With Burn Injury

Abstract: The objective of this study was to test the hypothesis that propranolol, a commonly prescribed β-blocker to burned children, in combination with exercise-heat stress, increases the risk of heat illness and exercise intolerance. In a randomized double-blind study, propranolol was given to 10 burned children, and placebo was given to 10 additional burned children (matched for TBSA burned; mean ± SD, 62 ± 13%), while nonburned children served as healthy controls. All groups were matched for age and body morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…It bears mentioning that, as we have recently reported, administration of the resting beta blocker, propranolol, does not affect exercise heart rate response and therefore burn children on propranolol can appropriately maintain the prescribed intensity of exercise during training sessions when heart rate is used to guide exercise intensity during exercise rehabilitation. 50 In summary, we found that boys with burn injury have similar relative body composition as burn-injured men at discharge and exercise training increases both lean and fat mass in both. We also found that, at discharge, boys experience a greater reduction in strength and cardiorespiratory fitness, with exercise training improving strength to a similar degree in boys and men and aerobic exercise capacity to a greater degree in men.…”
Section: Discussionmentioning
confidence: 54%
“…It bears mentioning that, as we have recently reported, administration of the resting beta blocker, propranolol, does not affect exercise heart rate response and therefore burn children on propranolol can appropriately maintain the prescribed intensity of exercise during training sessions when heart rate is used to guide exercise intensity during exercise rehabilitation. 50 In summary, we found that boys with burn injury have similar relative body composition as burn-injured men at discharge and exercise training increases both lean and fat mass in both. We also found that, at discharge, boys experience a greater reduction in strength and cardiorespiratory fitness, with exercise training improving strength to a similar degree in boys and men and aerobic exercise capacity to a greater degree in men.…”
Section: Discussionmentioning
confidence: 54%
“…Likewise, propranolol improves lean mass, strength, and peak VO 2 in children 37 . Notably, as we have recently reported, administration of propranolol does not affect exercise heart rate response and therefore, burned children taking propranolol can appropriately maintain the prescribed intensity of exercise during training sessions when heart rate is used to guide exercise intensity during exercise rehabilitation 33 . However, whether propranolol affects cardiovascular responses to exercise differently based on sex is unknown.…”
Section: Discussionmentioning
confidence: 72%
“…We previously showed that, during submaximal exercise, cardiac output is lower in burned children than nonburned age- and sex-matched children 32 . Additionally, burned children display signs of exercise intolerance and have a lower peak heart rate 32,33 . Notably, others have found that burn injury causes cardiac failure, particularly left ventricular myocardial depression in burned children 34 .…”
Section: Discussionmentioning
confidence: 99%
“…We have also found that propranolol administration does not impair muscle mass, strength, or VO 2 peak gained through an exercise program (36). Likewise, we recently found that propranolol administration did not affect the heart rate response to submaximal exercise, and therefore, subjects were able to maintain exercise intensity during the training sessions, as assessed using heart rate (38). Lastly, we analyzed children during puberty, and some of the enrolled patients may not have complete puberty before long-term testing.…”
Section: Discussionmentioning
confidence: 94%